STUDI AYAT-AYAT TENTANG PLURALITAS DAN KORELASINYA DENGAN OBJEK DAKWAH - Syaiful Arief (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2018)
The Qur'anic verses that speak of a plural society are numerous. The existence of this verse signifies that God Himself does not want any uniformity among his creatures. Plurality is a fact that must be accepted and addressed appropriately. This is because Islamic teachings not only belong to a certain nation at a certain time but it is a universal teaching. And da'wah should be propagated to all objects of da'wah. As the object of da'wah, human plurality requires the missionaries to always preach according to the condition of each object of da'wah. Awareness of this plurality also indirectly has a great correlation with the method used to preach to every object of da'wah. In this study it is found that the Qur'an provides guidance in preaching to be gentle, to say persuasive words, to give good advice, to invite dialogue, and not to force.